PENGGUNAAN GAMBAR KOMPUTER (COMPIC) DALAM MENGATASI KESULITAN MEMBACA PERMULAAN - Sidebang, Restio (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2019)
This research was conducted to improve learning in elementary schools. The problems in this action research include how (1) the characteristics of elementary school students who have difficulty reading, (2) the type and level of difficulty of reading elementary school students, (3) factors that cause students to have difficulty reading (4) the implementation of learning for children having trouble reading. The research objectives to be achieved are to identify the characteristics of elementary school students who have difficulty reading, the type and level of difficulty reading elementary school students, the implementation of Compic media learning for children having difficulty reading. The research method used is descriptive qualitative method with Classroom Action Research approach, the implementation of the study consisted of 3 cycles. Data collection is done through observation, tests, interviews and field notes. The research subjects in this study were first grade students of SD BPK PenaburTasikmalaya, as many as 6 people from 18 students.The results showed that: (1) identification of children having difficulty reading, the characteristics emerged and those that appeared from the child were reading slow, when asked about difficulties and many were silent, (2) The reading level of class I students was different, the type of difficulties indicated by 6 students there is a low reading level, (3) a factor that causes students to have difficulty reading comes from an environment that is less supportive of reading and self-factor knowledgealone, (5) learning outcomes of first grade children of SD BPK Penabur Tasikmalaya using Compic Media increased. The value of students who have difficulty reading there is an increase in the value of the initial reading significantly from the average value of the value of 4.5 to 6.5.Key Word: beginning reading, Compic, reading difficulties